Wanprestasi dalam Perjanjian Jual Beli Reyeng dengan Akad Istishna’ : (Studi di Desa Pringsurat Kecamatan Kajen Kabupaten Pekalongan) - Anggi Vira Agati; Mohammad Fateh; 'Alamul Yaqin; Muhammad Hamam (el hisbah: Journal of Islamic Economic Law, 2022)
The problem that often occurs in the sale and purchase agreement of reyeng in Pringsurat Village, Kajen District, Pekalongan Regency, is in the implementation of the agreement or contract, the seller and buyer agree to make transactions with payments made in advance, but in practice there is a default or broken promise in the form of late delivery of the goods. ordered by the buyer. So, there are two problems that become the main study in this study, namely: first, why does default occur in the sale and purchase agreement of reyeng; second, what are the legal consequences of default in the sale and purchase agreement of reyeng. Type of Research This is a field research using a legal sociology approach. Sources of data consist of primary and secondary data, primary data obtained by observation and interview techniques with the seller and buyer reyeng. while secondary data were obtained from other sources such as books, journal articles, theses, research results and other relevant documents that will be discussed by the author as a supporter. The results showed that the implementation of the istishna contract in buying and selling reyeng was in accordance with the pillars and terms of istishna, however, there were cases of default caused by negligence on the part of the seller. consequences arising from the existence of default in the sale and purchase agreement reyeng, namely the cancellation of the contract, payment of fines and compensation.